Correlations between Salivary Immuno-Biochemical Markers and HbA1c in Type 2 Diabetes Subjects before and after Dental Extraction - George-Alexandru Maftei (MDPI AG, 2021)
Dental extraction can trigger certain sequences of complex processes that involve both hard (alveolar bone) and soft tissue (periodontal ligament, gingiva) remodeling. Type 2 diabetes is a serious risk factor for many oral pathologies, both in terms of progression and severity, but also regarding subsequent rehabilitation possibilities. The aim of this study was to establish whether certain molecules: osteoprotegerin (OPG), kappa B nuclear factor receptor activator ligand (RANKL), hepatocyte growth factor (HGF), tumor necrosis factor-α (TNF-α), interleukin 18 (IL-18), matrix metalloproteinase 9 (MMP-9) and oxidative stress markers—total oxidant status (TOS), total antioxidant capacity (TAC)—evaluated in saliva are modified post-extraction in type 2 diabetes mellitus subjects and whether there is a correlation with HbA1c levels. The aforementioned markers plus HbA1c were investigated in a group of systemically healthy subjects (n = 45) and in a type 2 diabetes mellitus group (n = 41) before and three months after a tooth extraction. Diabetes patients’ recorded increased levels of OPG, RANKL, TNF-α, MMP-9, IL-18 and TOS compared to controls both pre- and post-extraction. In both study groups, the average OPG, HGF and TAC level recorded an upward trend three months post-extraction. TNF-α registered a statistically significant decrease only in the diabetes group after dental extraction, together with a decrement of mean HbA1c levels in the diabetes group. By plotting the ROC (receiver operating characteristic) curve, at baseline RANKL, TNF-α, IL-18, MMP-9, TOS and OPG were good predictors of HbA1c levels. Post-extraction, there was a significant correlation between HbA1c and oxidative status biomarkers, however the linear regression model indicated the influence of all studied salivary markers in HbA1c determinism, in a considerable proportion. In conclusion, our study demonstrated that several oxidative status markers and proinflammatory biomarkers are modified in the saliva of diabetic patients and they correlate to HbA1c levels, thus being potential indicators of the post-extraction healing status in the oral cavity.